Assessing and Adapting Rituals That Reproduce a Collectivity The Large-Scale Rituals of the Repkong Tantrists in Tibet - Sihlé, Nicolas (2018)
Tantrists, non-monastic religious specialists of Tibetan Buddhism, constitute a diffuse, non-centralized form of clergy. In an area like Repkong, where they present a high demographic density, large-scale supra-local annual ritual gatherings of tantrists are virtually synonymous with, and crucial for, their collective existence. In the largest of these rituals, the elders' meeting' is in effect an institutionalized procedure for evaluating the ritual performance, its conditions and effects, and, if necessary, for adjusting aspects of the ritual. At a recent meeting, the elders' decided to abandon a powerful and valued but violent and problematical component of the ritual, due to its potential detrimental effects on the fabric of social relations on which the ritual depends for its continued existence. Thus, a highly scripted, liturgy-centered' ritual (per Atkinson) can be adapted to the social context. The specialists of these textual rituals demonstrate collectively an expertise that extends into the sociological dynamics surrounding the ritual.
Keywords: Tibetan Buddhism; Conflict; liturgical ritual; ritual aggression; ritual assessment; ritual change; Ritual violence; tantrists